Pengaruh Budaya Organisasi dan Perceived Organizational Support terhadap Work Engagement Pada Karyawan Perusahaan Industri Manufaktur di Kota Bandung - Elma Aurelia Agustine; Nina Nurani (BRILIANT: Jurnal Riset dan Konseptual, 2026)
This study aims to determine whether organizational culture and perceived organizational support influence work engagement among employees working in the manufacturing industry. The research subjects were employees actively working in manufacturing companies in Bandung City. Through a nonprobability sampling technique, 228 employees working in the manufacturing industry in Bandung City were obtained. Data were analyzed using multiple linear regression methods to test the relationship between variables. The research findings show that organizational culture and perceived organizational support have a positive and significant effect on work engagement. This means that companies with a positive organizational culture that emphasizes caring, clear work targets, management systems, and responsibility can foster employee enthusiasm and engagement with their work. Furthermore, when employees feel that the company cares, values ​​their contributions, and supports their well-being, this can foster positive reciprocal relationships and lead employees to be more enthusiastic, focused, and involved in their work. The results of this study can be implied by the management of manufacturing companies for the development of human resource programs.